2018
DOI: 10.15212/fmch.2018.0115
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between glycemic control and perceived family support among people with type 2 diabetes mellitus seen in a rich kinship network in Southwest Nigeria

Abstract: Objective: The practice of diabetes self-care behaviors has been cited as a foundation for achieving optimal glycemic control. Proper motivation of people with diabetes mellitus is, however, needed for the performance of these behaviors. It is therefore pertinent to know if motivation by the family will improve glycemic control in people with type 2 diabetes mellitus. This study aimed to investigate the relationship between glycemic control and perceived family support among Nigerians with type 2 diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
2
12
2
4
Order By: Relevance
“…Five studies assessed the relationship between increasing age and glycaemic control [ 27 , 31 , 34 , 58 , 61 ], two found that it was negatively associated with glycosylated haemoglobin [ 31 , 61 ], and one found that it was associated with good glycaemic control [ 57 ]. Older age was associated with poor glycaemic control in twelve studies [ 22 , 29 , 32 , 36 , 39 , 65 , 68 , 69 , 73 , 77 , 83 , 86 ]. Eight studies assessed the relationship between the female gender and glycaemic control [ 18 , 29 , 34 , 51 , 61 , 64 , 65 , 73 ], two studies found that the female gender was significantly associated with poor glycaemic control [ 18 , 34 ], and one study linked it to good glycaemic control [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies assessed the relationship between increasing age and glycaemic control [ 27 , 31 , 34 , 58 , 61 ], two found that it was negatively associated with glycosylated haemoglobin [ 31 , 61 ], and one found that it was associated with good glycaemic control [ 57 ]. Older age was associated with poor glycaemic control in twelve studies [ 22 , 29 , 32 , 36 , 39 , 65 , 68 , 69 , 73 , 77 , 83 , 86 ]. Eight studies assessed the relationship between the female gender and glycaemic control [ 18 , 29 , 34 , 51 , 61 , 64 , 65 , 73 ], two studies found that the female gender was significantly associated with poor glycaemic control [ 18 , 34 ], and one study linked it to good glycaemic control [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there has been inconsistency on the influence of sex on glycaemic control. Some authors reported better control in female diabetic patients [20,38,39] while another study reported better control in the males. The reason for this variation was attributed to the very low socioeconomic status of the women in the study setting [40].…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, Osuji et al in southwestern Nigeria studied the relationship between perceived family support and glycaemic control. The authors of Osuji et al study reported that patients with high perceived family support had better glycaemic control [20]. To the best of knowledge of the authors, no study has been done in the study hospital on the relationship between perceived family support and the control of type 2 diabetes mellitus (T2DM) in adults.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in contrast to the widely reported poor glycemic control among diabetes patients in Southern Nigeria, as supported by preceding literature. For instance, as high as 59.4% of poor glycemic control has been reported (Osuji and Odebunmi, 2013), 55% (Ufuoma and Ngozi, 2016) and Fiseha and co-workers also reported an overwhelming 71% poor glycemic control among diabetes patients in a hospital-based cross-sectional study in North-eastern Ethiopia (Fiseha and Gebreweld, 2018). Similarly, in Asia, Li et al reported inadequate glycemic control (50.3%) among Type 2 diabetes patients attending tertiary healthcare facility in Ningbo, China (Li www.jBiomedAnalytics.org and Li, 2018).…”
Section: Discussionmentioning
confidence: 99%